Association of Non-Cigarette Tobacco Advertisements and Racial Discrimination With Non-Cigarette Tobacco Product Use Among Black Adults. Issue 4 (28th September 2022) - Jackson, Asti; Fleischli, Mary E; Haeny, Angela M; Rose, Shyanika W; Fagan, Pebbles; Krishnan-Sarin, Suchitra; Gerrard, Meg; Gibbons, Frederick X
Abstract: Introduction: Black communities are targeted by more cigarette advertisements than White communities and racial discrimination among Black people is related to cigarette use. However, little is known about these factors with non-cigarette tobacco product use among Black adults. Therefore, this study assessed the association of non-cigarette advertisement exposure and racial discrimination with use of non-cigarette tobacco products among Black adults. Aims and Methods: Black adults ( n = 533) from The Family and Community Health Study in 2016 were asked if they had seen advertisements for e-cigarettes, snus pouches, filtered cigars, large cigars, cigarillos, dissolvable tobacco, smokeless tobacco, hookah, and tobacco pipe and if they used these in the past month. For products with the highest past month use and significant correlations with advertisement exposure, separate logistic regression models were performed that evaluated the association between advertisement exposure, racial discrimination, and non-cigarette tobacco product use while controlling for cigarette use, sex, socioeconomic status, and age. Results: Use of cigarillos, large cigars, and hookah were higher than other non-cigarette tobacco products assessed. Logistic regressions revealed that more advertisement exposure in the past month was associated with higher odds of using cigarillos, large cigars, and hookah ( p < .01). More experiences of racial discrimination were associated with past month cigarillo use, but not hookah or large cigars ( p < .01). Conclusions: Non-cigarette tobacco advertisement exposure was associated with the use of non-cigarette tobacco products. Experiences of racial discrimination were associated with the most used non-cigarette tobacco product among Black adults, cigarillos. Implications: This is the first time that a specific type of cigar (ie cigarillos) has been associated with experiences of racial discrimination among Black adults. Efforts to reduce non-cigarette tobacco marketing and eradicate exposure to racial discrimination among Black adults may aid in eliminating tobacco-related health disparities.